Seasonality and household diets in Ethiopia - Hirvonen, Kalle; Taffesse, Alemayehu Seyoum; Worku, Ibrahim (Cambridge University Press, 2016)
To revisit seasonality by assessing how household diets vary across agricultural seasons in rural and urban Ethiopia. The role of seasonality on the sources and intake of energy (per capita) and household dietary diversity score (HDDS) was analysed.The use of nationally representative household-level data collected each month over one year to study the seasonal changes in the sources and intake of energy and HDDS.Eleven regions of Ethiopia, including rural and urban settings.Total of 27 835 households were interviewed between July 2010 and July 2011 in all eleven regions of the country. On average each month saw 2300 household interviews, yielding nationally representative data for each calendar month.For rural households, the mean daily per capita energy intake was 10 288 kJ (2459 kcal) in February (post-harvest period) and lower in the lean season: 9703 kJ (2319 kcal) in June (P<0·05) and 9552 kJ (2283 kcal) in July (P<0·001). HDDS for rural households was highest in February (6·73) and lowest in June (5·98; P<0·001) but high again in July (6·57). Urban energy intake was also lower in the lean season but HDDS varied less by season. Considerable seasonal variation was also found in energy sources in rural areas, less so in urban areas.Household diets in Ethiopia remain subjected to significant seasonal stress. HDDS and food security measured using energy intake do not always agree. Preferably, HDDS and energy intake data should be used together to assess food security.